PENGARUH MARKETING MIX TERHADAP KEPUASAN KONSUMEN (PADA HOME INDUSTRY MOSHIMOSHI CAKE SAMARINDA) - firdayanti abbas (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2020)
The purpose of this study was to know marketing mix influence on consumer satisfaction in home industry MoshiMoshi Cake Samarinda. To know the variables of the marketing mix (product, price, promotion and place) the more dominant influence on customer satisfaction in the industry home MoshiMoshi Cake Samarinda. While the methods used are descriptive analysis, multiple linear regression analysis, and test hepotesis. Based on the analysis about effect between the marketing mix (product, price, promotion and place) to consumer satisfaction in home industry MoshiMoshi Cake Samarinda. The most dominant variable affecting customer satisfication is place, because the place of sale from MoshiMoshi cake is strategically located, easily accessible, and always visited by potential costumers.